Portrait of class management in the learning process at Muhammadiyah Kretek Middle School: A qualitative descriptive study - Arwinda, Alda; Ferawati, Denny Indria (DRPM UNY, 2025)
The importance of effective classroom management has emerged as a critical factor in enhancing student learning motivation, particularly in the context of rapidly evolving educational environments. This study aims to explore the role of classroom management in improving student motivation through a qualitative descriptive approach. The research was conducted at Muhammadiyah Kretek Middle School in Bantul, with all classes at the school serving as research subjects. Data were collected using observation, interviews, and documentation techniques. The findings indicate that classroom management by teachers has not been fully optimized, and the teaching methods employed remain relatively monotonous, which leads to students' decreased engagement in the learning process. However, teachers continue to make efforts to improve classroom management through thorough preparation of learning materials, varied teaching methods, strategic seating arrangements, and incorporating playful learning activities. Additionally, teachers are working to integrate advancements in science and technology to create a more engaging and dynamic learning environment, aiming to reduce the monotony in the classroom.